Microstructure and long-term stability of solder joints on nickel-plated aluminium formed during short soldering times. Issue 66 (4th November 2020) - De Rose, Angela; Mikolasch, Gabriele; Kamp, Mathias; Kraft, Achim; Nowottnick, Mathias
Abstract : High mechanical reliability of tin-based solder joints processed by joining copper and nickel-coated aluminium with short soldering times in ambient air. Abstract : Within this work, we demonstrate that an easy soldering process in combination with wet chemical coating is suitable to realize a strong and reliable solder interconnection of Al substrates, even at short soldering times <5 s in ambient air. The microstructure of solder joints on wet chemically treated aluminum foils is investigated. A single and double zincate pre-treatment are compared to activate the Al surface, followed by electroless Ni plating. The quality of the solderable Ni surface is characterized by contact angle measurements, yielding good wettability (<60°), which is also achieved after isothermally heating (250 °C) the Ni-coated Al foils for 100 min. The microstructure of the Sn62Pb36Ag2 solder joints is investigated by SEM and EDX of cross sections, directly after soldering as well as after isothermal aging at 85 °C. Under the used soldering conditions, with a soldering temperature at about 280 °C, diffusion zones <500 nm were identified. Nonetheless, high peel forces after soldering >5 N mm −1 show stable values under aging conditions of 85 °C for 1000 hours. This could be correlated to a mixed fracture pattern, promoting the high adhesion due to the absence of a dominant failure mechanism.